1999
DOI: 10.1046/j.1439-0507.1999.00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of dermatophytes by Fourier transform infrared spectroscopy (FT‐IR)

Abstract: Fourier transform infrared spectroscopy is an established method in the routine diagnosis of various micro-organisms, including bacteria and yeasts, on a species level. Its possible value in the diagnostics of dermatophytes was analysed using three clinical isolates each of the three most frequently found species, namely Trichophyton rubrum, Trichophyton mentagrophytes and Microsporum canis. The results encourage further work to establish a library which would allow the use of this method in the clinical setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 11 publications
(2 reference statements)
0
14
0
6
Order By: Relevance
“…Various studies have shown the applicability of FTIR spectroscopy to classify and identify bacterial and fungal microorganisms as well as prions (1,4,5,10,21,28). Furthermore, FTIR spectroscopy was used successfully as a fingerprinting technique for the assessment of intraspecies variability (7,13,22).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown the applicability of FTIR spectroscopy to classify and identify bacterial and fungal microorganisms as well as prions (1,4,5,10,21,28). Furthermore, FTIR spectroscopy was used successfully as a fingerprinting technique for the assessment of intraspecies variability (7,13,22).…”
Section: Discussionmentioning
confidence: 99%
“…At the time of the study, the individual test centers applying routine standard laboratory procedures performed the initial species identification, and species confirmation was performed using Fourier transform infrared spectroscopy (FT-IR). FT-IR has been reported to be a rapid, reliable, and cost-saving tool to identify and differentiate bacteria, dermatophytes, and yeasts (54)(55)(56)(57)(58)(59)(60)(61)(62). An IFS 28/B spectrophotometer (Bruker GmbH, Germany) was used for FT-IRbased identification; the resulting spectra were transformed and evaluated using Opus software from Bruker GmbH, as previously described by Tietz et al (58).…”
Section: Methodsmentioning
confidence: 99%
“…Various fungal genera have been identified by using dry spores, fruit bodies or cultural biomass as source material for FTIR. These include Aspergillus [2], Mucor [11], Penicillium [2,12], Memnoniella, Fusarium [12] and dermetophytes [13] and certain wood fungi [14], food spoilage fungi [15] and mushrooms genera such as Agaricus, Amanita, Lactarius, Macrolepiota and Pleurotus [8]. Fungal cell wall structure and chemical composition is found to be diverse from species to species and .…”
Section: Introductionmentioning
confidence: 99%